THE DEVELOPMENT OF EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) IMPLEMENTATION IN CHEMISTRY EDUCATION: A LITERATURE REVIEW - Munawwarah M; Hastuti Agussalim (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
This study presents a systematic literature review of the implementation of Education for Sustainable Development (ESD) in chemistry education between 2012 and 2025. A total of 15 articles were analyzed, encompassing both international and national studies, with the aim of mapping theoretical models, instructional innovations, and student outcomes within the framework of ESD. The findings reveal that research in this area can be categorized into two major contributions: conceptual contributions, which focus on developing models, frameworks, and didactic theories, and practical contributions, which emphasize instructional media, laboratory modules, contextual teaching tools, and project-based learning strategies. Practical contributions dominate the literature, demonstrating significant impacts on students’ chemistry literacy, creativity, and sustainability awareness. However, competencies such as critical thinking, problem-solving, and action competence remain underexplored and insufficiently assessed. The review further highlights that while teachers and pre-service teachers generally show positive attitudes toward ESD, their understanding often remains limited to environmental dimensions, underscoring the need for more comprehensive professional preparation. These findings suggest that future research should adopt a more balanced agenda that integrates conceptual development with practical innovations, while systematically fostering a broader spectrum of sustainability competencies. In conclusion, chemistry education holds substantial potential to contribute not only to the mastery of scientific knowledge but also to the cultivation of responsible citizens equipped to address the complex challenges of sustainable development.